Asian Bush Mosquito, Asian Rock Pool Mosquito Aedes japonicus japonicus (Theobald, 1901) (Insecta: Diptera: Culicidae) - Catherine Lippi; Phillip E. Kaufman; Eva A. Buckner (EDIS)
Contents: Introduction - Synonymy - Distribution - Life Cycle - Medical Importance - Surveillance and Management - Selected References